The impact of COVID-19 on transportation aspects of trade between China and Japan - Michovský, Petr (2024)
The COVID-19 pandemic has profoundly affected global economies and transport networks, revealing the vulnerabilities and strengths of critical infrastructure. This thesis examines bilateral trade relations between China and Japan, focusing on the impact of the pandemic on the transport sectors and their role in sustaining trade. China's centralized zero COVID policy maintained freight continuity despite severe restrictions, but highlighted challenges in adapting during rapidly evolving circumstances. Japan's reliance on voluntary measures and robust infrastructure mitigated some disruptions, but its air transport sector faced significant volatility compared to more resilient maritime trade. The analysis identifies key shifts in trade patterns, employment trends and sector resilience, highlighting China's growing domestic production capacity and Japan's reliance on imports. Both countries have demonstrated the ability to adapt in response to supply chain disruptions, supported by government intervention and investment in transport. However, the findings highlight the need for strategic infrastructure investments that balance efficiency, sustainability and adaptability to future crises. This study contributes to the understanding of the critical role of transport in international trade and offers insights for enhancing the resilience of global supply chains.